Morphology tuning of bismuth oxychloride nano-crystals by citric acid variation: Application in visible light-assisted dye degradation and hydrogen evolution by electrochemical method. (29th April 2021) - Sarkar, Ratna; Roy, Dipayan; Das, Dimitra; Sarkar, Subrata; Chattopadhyay, Kalyan K.
Abstract: Bismuth Oxychloride (BiOCl) is a p-type indirect bandgap semiconductor with gaps in the range of 3.2–3.5 eV. In this work, BiOCl was synthesized by a simple hydrothermal method along with variation in the concentration of the capping agent citric acid to perform the tuning of the morphology of the samples. The samples were analyzed by various techniques for insight into phase formation, morphology, chemical composition etc. The as-synthesized nanomaterials exhibited extensive variation in crystal structures due to variation in the citric acid ratio. Finally the as-synthesized samples were utilized for effective photocatalytic degradation of toxic textile dyes like Rhodamine B under visible light irradiation and also for hydrogen evolution by electrochemical method. The structural tuning resulted in a noticeable increment in hydrogen evolution observed in an acidic medium for a low overpotential. The as-synthesized material can thus be utilized for waste-water remediation and various electrochemical water-splitting related applications. Graphical abstract: Image 1 Highlights: Nanonut-like BiOCl with exposed (001) facets was prepared by a hydrothermal route. Complete photo-degradation of Rhodamine B dye under visible light within 10 min. A photocatalytic mechanism was proposed. BiOCl also exhibited hydrogen evolution by electrochemical water splitting.